Initial diagnosis of HIV/AIDS in a 56-year-old man with non-healing forearm lesion. - Zapata, Heidi J; Villanueva, Merceditas; Shenoi, Sheela (BMJ case reports, 2013)
A 56-year-old Hispanic man with no significant medical problems presented with a 2-month history of a non-healing right forearm lesion that progressed despite several courses of empiric antibiotics. The patient underwent incision and drainage. Warthin-Starry stain with immunohistochemistry testing diagnosed bacillary angiomatosis secondary to Bartonella quintana. Subsequently, the patient was diagnosed with HIV, with a CD4 count of 68 cells/mm(3), and a HIV viral load of 47, 914 copies/mL. The patient was treated with doxycycline and started on antiretroviral therapy. The lesion has resolved and he has had no recurrence after 16 months of treatment.